The reliability and quality of short videos as health information of guidance for lymphedema: a cross-sectional study - Zhou, Xuchuan; Ma, Gejia; Su, Xuefeng; Li, Xinyi; Wang, Wenfei; Xia, Linxi; Yang, Chen; Liu, Bin (Frontiers in Public Health, 2025)
BackgroundThe prevalence of lymphedema is rising, necessitating accurate diagnostic and treatment information for affected patients. Short video-sharing platforms facilitate access to such information but require validation regarding the reliability and quality of the content presented. This study aimed to assess the reliability and quality of lymphedema-related information on Chinese short video-sharing platforms.MethodsWe collected 111 video samples addressing the diagnosis and treatment of lymphedema from four platforms: TikTok, Bilibili, WeChat, and Microblog. Two independent surgeons evaluated each video for content comprehensiveness, quality (using the Global Quality Score), and reliability (using the modified DISCERN tool). The videos from different sources were subsequently compared and analyzed.ResultsOut of 111 videos analyzed, 66 (59.46%) were uploaded by medical professionals, including breast surgeons, vascular surgeons, plastic surgeons, physical therapists, and gynecologists, while 45 (40.54%) were shared by non-medical professionals such as science bloggers, medical institutions, and lymphedema patients. Patient-uploaded videos received the highest engagement, with median likes of 2,257 (IQR: 246.25–10998.25) and favorites of 399 (IQR: 94.5–1794.75). 13 videos (11.71%) contained inaccuracies. Medical professionals’ videos generally showed higher content comprehensiveness, particularly those by plastic surgeons, compared to non-medical professionals. The GQS and modified DISCERN tool were used to assess video quality and reliability respectively, with medical professionals scoring higher on both metrics (z = 3.127, p = 0.002; z = 2.010, p = 0.044). The quality and reliability of recommendations provided by plastic surgeons surpassed that of other medical professionals (χ2 = 16.196, p = 0.003; χ2 = 9.700, p = 0.046). No significant differences in video quality and reliability were found among the three categories of non-medical professionals (χ2 = 3.491, p = 0.175; χ2 = 2.098, p = 0.350).ConclusionOur study shows that lymphedema-related videos on short video platforms vary widely in quality. Videos by medical professionals are generally more accurate and of higher quality than those by non-professionals. However, patient-uploaded videos often get more engagement due to their relatability. To ensure public access to reliable information, establishing basic standards for this content is essential.